Does green finance support to reduce the investment sensitivity of environmental firms? - Habib, Ashfaq; Khan, Muhammad Asif; Oláh, Judit (Journal of Business Economics and Management, 2023)
This study aims to examine the financing cash flow sensitivity into the firm investment of Environment Sensitive Firms (ESFs). To improve the robustness of our analysis, we implement cluster regression to analyze the 300- firms listed on Shenzhen Stock Exchange. The findings of this study indicate that high-ESFs have more financing cash flow volatility in firm investment than low-ESFs. The firms can reduce this volatility by integrating green finance with their financing cash flows. Green finance helps to implement sustainable investment practices and reduces investment volatility by providing the solution to societal issues. It also assists to generate stable cash flows, lower investment risk, and a better governance structure.